2019
DOI: 10.1073/pnas.1819467116
|View full text |Cite
|
Sign up to set email alerts
|

Comparing signals of natural selection between three Indigenous North American populations

Abstract: While many studies have highlighted human adaptations to diverse environments worldwide, genomic studies of natural selection in Indigenous populations in the Americas have been absent from this literature until very recently. Since humans first entered the Americas some 20,000 years ago, they have settled in many new environments across the continent. This diversity of environments has placed variable selective pressures on the populations living in each region, but the effects of these pressures have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 45 publications
3
40
0
1
Order By: Relevance
“…We intersected results from PBS and iHS to pinpoint SNVs most likely to be under selection, since PBS can detect signals of selection [ 36 ], while iHS allows us to detect selective sweeps for very recent selection events [ 37 , 38 ]. The intersection between both methods reduces false positive signals by taking into account the demographic history factor underlying the iHS analysis, a common confusion factor in FST based approaches [ 9 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We intersected results from PBS and iHS to pinpoint SNVs most likely to be under selection, since PBS can detect signals of selection [ 36 ], while iHS allows us to detect selective sweeps for very recent selection events [ 37 , 38 ]. The intersection between both methods reduces false positive signals by taking into account the demographic history factor underlying the iHS analysis, a common confusion factor in FST based approaches [ 9 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This fast expansion along a 16 thousand kilometers North-South axis into an uninhabited continent, is unparalleled in the history of human groups [ 3 , 5 ].The peopling of the continent was complex and there is evidence of back-migrations along other interesting population movements [ 5 ]. Genetic changes that took place in these new ecosystems were certainly swift and with far reaching consequences, leaving marks in the genomes of present day NatAm [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Working with ancient and contemporary populations from North America and Peru, researchers have shown that at least a 50% decline of Indigenous populations is detectable among maternal genetic lineages beginning approximately 500 years ago (O'Fallon and Fehren-Schmitz 2011). Subsequent studies among ancient and contemporary communities elsewhere in the Americas have largely confirmed this (Lindo et al 2016(Lindo et al , 2018Reynolds et al 2019). While mortality among Indigenous peoples is already known from the archives of archaeology and history, as well as Indigenous peoples' own memory, this recent genetic research holds significant implications for the impacts of colonization on genetic variation in the Americas.…”
Section: Imperial Terroir and The Molecular Impacts Of Colonization Amentioning
confidence: 87%
“…Connecting colonization to its genetic impacts also has implications for the emergence of health inequalities among contemporary Indigenous populations. For example, recent studies in the Pacific Northwest, US Southeast, and Mexico have linked epidemics introduced by European colonizers with shifts in genes related to adaptive immune function (Lindo et al 2016;Reynolds et al 2019). In addition to these genetic effects, researchers working under the framework of historical trauma (Brave Heart 1998) have noted that grief and feelings of loss related to culture, land, and language impact the health of Indigenous people today (Whitbeck et al 2004).…”
Section: Imperial Terroir and The Molecular Impacts Of Colonization Amentioning
confidence: 99%
“…The haplotype-based statistic, iHS, is often used to detect signatures of recent positive selection and partial selective sweeps (Voight et al, 2006), particularly in non-admixed populations. This statistic has been used as evidence of selection in recently admixed populations (V. Fernandes et al, 2019;Norris et al, 2020;Reynolds et al, 2019). However, the process of admixture results in the mixture of differentiated allele frequencies and diverged haplotypes, so interpretation of these statistics is difficult and applicability is limited.…”
Section: Classical Haplotype-based Signatures Of Selection Not Detectmentioning
confidence: 99%